A novel soft tissue cone-beam computed tomography study in the evaluation of gingival thickness associated with subepithelial connective tissue graft versus acellular dermal matrix in the management of gingival recession: A clinical study - Nimisha Mithradas; Uma Sudhakar; Lalitha T Arunachalam; Snophia Suresh; Manoj Raja (Wolters Kluwer Medknow Publications, 2020)
Background: Dental esthetic awareness among patients led the clinicians to introduce newer materials and predictable techniques that satisfy the patients' esthetic demands. Aim: To evaluate and compare the efficacy of subepithelial connective tissue graft (SECTG) and acellular dermal matrix (ACDM) allograft in the treatment of Millers Class I or Class II recession with the determination of gingival thickness using an impertinent method, soft tissue cone-beam computed tomography (ST-CBCT). Materials and Methods: A split-mouth study with a total of ten patients with bilateral Millers class I or class II recession is randomly assigned by a coin toss method as Group I (SECTG) and Group II (ACDM) along with coronally advanced flap. Clinical parameters including recession height (RH), recession width (RW), probing depth, clinical attachment level (CAL), and height of keratinized tissue (HKT) were evaluated at baseline, 90th day, and 180th day for both groups. The thickness of keratinized tissue (TKT) was determined by most reliable, predictable and noninvasive method called ST-CBCT. Results: Statistically significant reduction in RH and RW, gain in CAL, and increase in HKT and TKT in both Group I and Group II were seen in 90th day and 180th day. However, when both Group I and Group II were compared between 0 and 180th day, the change in RH and RW, gain in CAL, and increase in HKT and TKT did not show any statistically significant change. Conclusion: The present study suggested that root coverage with both SECTG and ACDM is very predictable procedure and it is stable for 6 months. ST-CBCT is a newer dimension in periodontal imaging and will certainly aid clinicians in the execution of various treatment modalities with increased predictability.